Review Workshop. Implementation results and scaling Agro-Climatic Bulletins (ACB) in Mekong River Delta - Le Thi Tam; Nguyen Mai, Huong (2022)
This report presents the implementation results and scaling of agro-climatic bulletins (ACB) in the Mekong River Delta in Vietnam based on the experience of seven provinces. Participants and the government discussed the options on how to sustain project outcomes and approaches introduced as well as opportunities to enhance the current gap in climate services in the agriculture sector.